Ludność parafii Rembieszyce po II wojnie światowej w świetle ksiąg metrykalnych - Karkocha, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2014)
The article aims to discuss the most important demographic phenomena occurring in the Roman Catholic Parish of Rembieszyce after World War II, in the years 1945–2012. The basic sources for the Author were the parish registers of births, marriages and deaths, stored in the Archive of the Rembieszyce Parish. It was studied the collection of 2490 metrics of baptisms, 997 metrics of weddings, and 1272 metrics of funerals, making a total amount of 4759 metrical acts. The Author had identified three key issues, i.e. births, marriages and deaths. Each of these problems has been characterized mainly by specifying the level of the phenomenon and its seasonality. In addition, with respect to the births, it was discussed the structure of births by localities, multiple births, the popularity of male and female names, as well as habits of giving the names and choice the godparents. The image of weddings also consists: the structure of the prospective spouses by age, marital status and territorial mobility of newlyweds. By contrast, analysis of deaths and funerals was complemented by the structure of deceased persons by sex and age, the life expectancy for men and women, the causes of death, and the issue of the last sacraments. At the end of the article was presented the natural growth and loss of the population of the Rembieszyce Parish.